Myrmoplastoides subgen. nov. of the genus Myrmoplasta (Hemiptera: Heteroptera: Pyrrhocoridae) from the Oriental region - Stehlík, Jaroslav L.; Kment, Petr (Zootaxa, 2008)
Myrmoplasta Gerstäcker, 1892, is a small genus of the family Pyrrhocoridae, currently including five described species—Myrmoplasta mira Gerstäcker, 1892, M. vittiventris Carlini, 1894, and M. kmenti Stehlík, 2007, from the Afrotropical region (Stehlík 2007); and two Oriental species, M. longipennis Blöte, 1933, and M. biguttata Blöte, 1933, both known only from the short original descriptions by Blöte (1933). The examination of types of both Oriental Myrmoplasta species enable us to redescribe them, and to describe the hitherto unknown male of M. longipennis. Moreover, we found several important differences between the Oriental and the Afrotropical species of the genus, which warrant the establishing of a new subgenus—Myrmoplastoides subgen. nov.—for the Oriental species.